Comparative Numerical Studies of Electromechanical Finite Element Vibration Power Harvester Approaches of a Piezoelectric Unimorph - Eziwarman, Eziwarman; Lumentut, Mikail; Howard, Ian (IEEE, 2014)
Emerging micro-power harvester research using smart material components shows viable self-powered devices capable of capturing mechanical motion and converting it into useful electrical energy that can be further used to supply electrical voltage into rechargeable power storage via a power management electronic circuit. The micro-power harvesters using piezoelectric materials cover a wide range of applications for powering thin film battery technology and wireless sensor systems that can be used to monitor the health condition of machines and infrastructure and biomedical implant devices. This research focuses on the development of a novel numerical direct method technique with non-orthonormality based on the electromechanical vector transformation for modelling the self-powered cantilevered piezoelectric unimorph beam under input base excitation. The proposed finite element piezoelectric unimorph beam equations were formulated using Hamiltonian’s principle for formulating the global matrices of electromechanical dynamic equations based on the electromechanical vector transformation that can be further employed to derive the electromechanical frequency response functions. This numerical technique was modelled using electromechanical discretisation consisting of mechanical and electrical discretised elements due to the electrode layers covering the surfaces of the piezoelectric structure, giving the single voltage output. The reduced equations are based on the Euler-Bernoulli beam assumption for designing the typical power harvesting device. The proposed finite element models were also compared with orthonormalised electromechanical finite element response techniques, giving accurate results in the frequency domains.